Poor Outcome of Right Bundle Branch Block Coexist with ST-Elevation Myocardial Infarction - Arifta Devi Anggraeni; Andrianto Andrianto; Ivana Purnama Dewi; Eka Prasetya Budi Mulia; Anudya Kartika Ratri (Heart Science Journal, 2022)
BACKGROUND: The incidence of new-onset right bundle branch block (RBBB) coexistence with ST-elevation myocardial infarction (STEMI) has been associated with higher in-hospital mortality compared with those without RBBB.CASES: We present three cases of new-onset RBBB coexist with STEMI. Case I: a 64 years old male presented Killip I STEMI inferior-anterior with RBBB as new-onset. Rescue percutaneous coronary intervention (PCI) after failed thrombolytic was performed. New-onset atrial fibrillation (AF) with rapid ventricular response worsened his hemodynamic profile, leading to cardiogenic shock. Case II: an 80 years old male presented Killip IV late-onset anterior STEMI with new-onset RBBB. Cardiogenic shock got worsened after PCI stent. Case III: a 65 years old male presented Killip II extensive anterior STEMI with new-onset RBBB who underwent a primary PCI stent. Recurrent ventricular tachycardia (VT), worsening cardiogenic shock, and transient AV block occurred after PCI. The right bundle branch blood supply is mainly provided by a septal branch of left descending artery (LAD). Therefore, it may indicate proximal LAD occlusion and extensive infarction. Thus, catastrophic events may occur, which including acute heart failure, AV block, malignant ventricular arrhythmia, new-onset AF, and mostly cardiogenic shock, despite initiate reperfusion was performed without delay once the diagnosis is confirmed.  CONCLUSION: New RBBB suggests poor short-term prognosis due to its complication. Higher mortality is mostly linked to worsening cardiogenic shock.